Trabalho infantil esportivo e artístico: o sentido a partir da vivência - Belém, Kássia Kiss Grangeiro (2015)
The sports and artistic child labor is sometimes not considered as such because the fame is not displayed damage to development. It should be noted as well the social and theoretical relevance of this dissertation. It should be noted as well the social and theoretical relevance of this dissertation. Having as the general objective is to analyze the meaning of sports and artistic child labor from the perspective of those who experience or have experienced these work activities and their implications. And the following objectives: characterize the biosociodemographic profile of the children/adolescents and adults who experience/experienced these forms of child labor, the implications of the sporting and artistic child labor for those who experience or who experienced; to analyze the experience in the sports and artistic child labor; the relation between living conditions and child labor; to identify the meaning of work in an environment that involves fame and financial advancement and the life project of this children/adolescents and adults at the time they worked. Is adopted as an approach to historical-cultural theory of Vygotsky, specifically the categories sense, meaning, experience and life project. The participants were children/adolescents and adults who experience or experienced sports or artistic child labor. To determine the sample size, we used the criterion of saturation. It was used as a tool to semi-structured interviews and to analyze the data used a association map of ideas. Was interviewed 19 people, twelve male and seven female. The ages at which entered the career ranged between 4 and 16 years. Stand out as implications grown up early, injury, impaired school performance and social life. Regarding to the meaning of the activities the artists conceive as work and athletes conceive leisure. It is necessary to understand the ceiling that separates the activity that is beneficial to the development and what is child and adolescents exploration.